TiB whisker induced variant selection in titanium matrix composites. (August 2022) - Le, Jianwen; Boehlert, C.J.; Huang, Guangfa; Mao, Jianwei; Lei, Liming; Han, Yuanfei; Lu, Weijie
Abstract: Considerable studies confirmed the existence of multiple orientation relationships (ORs) between TiB whiskers and α precipitates in titanium matrix composites (TMCs), but the role of TiB on α variant selection has not been demonstrated. In this study, three preferred ORs between TiB and α variants were obtained from β heat-treated TMCs by analyzing the misorientation angle/axis distributions, thereby confirming the selection of TiB whiskers for α variants. It was found that the grain refinement and equiaxed effect of TiB whiskers on the matrix microstructure are mainly reflected in the selected α variants. The dependence of the variant-selection degree on the cooling rate was investigated and the strongest variant selection of TiB whisker occurred at a cooling rate of 1°C/s. In addition, reconstruction of the parent β-phase revealed that the selected α variants heterogeneously nucleate from TiB and do not exhibit the Burgers relationship with the parent β phase. Graphical abstract: Image, graphical abstract